2016
DOI: 10.3390/su8111200
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Direction on the Environmental and Business Performance Relationship at the Firm Level. Lessons from a Literature Review

Abstract: Abstract:The interest of scientists and companies in understanding the business implications of environmental investment is timely; however, a dilemma remains at the firm level: is the environment a "strategic competitive factor", as in the "Porter point of view", or is it a "luxury good", as in the "Wagner point of view"? Our research contributes to this debate through a review of the papers published in scientific journals between 2000 and 2015 that discussed the direction of the relationship between the env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 112 publications
(147 reference statements)
0
28
0
Order By: Relevance
“…Due to the differences in the results, it is interesting to quote an in-depth literature review by Mazzi et al [126]. They analysed papers published in scientific journals between 2000 and 2015, concerning the direction of the relationship between the environmental and business performances of enterprises from various fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the differences in the results, it is interesting to quote an in-depth literature review by Mazzi et al [126]. They analysed papers published in scientific journals between 2000 and 2015, concerning the direction of the relationship between the environmental and business performances of enterprises from various fields.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that it is not possible to find an answer to the "Porter-Wagner dilemma" (is the environment a "strategic competitive factor", as in the "Porter point of view", or is it a "luxury good", as in the "Wagner point of view"?). The main reason for the unclear results was-according to Mazzi et al [126]-the adoption of different indicators, which could not be overcome even by rigorous methods of analysis. It seems that clear and comparable results can be obtained only with the use of universal indicators.…”
Section: Discussionmentioning
confidence: 99%
“…One study [43] mentioned that "88% of consumers said they were more likely to buy from a company that supports and engages in activities to improve society (CSR activities)". Mazzi et al [44] mentioned that the relationship between environmental performance (EP) and business performance (BP) is even more relevant from the firms' perspective, since companies have great interest in learning about the economic benefits of environmental responsibility. In the case of Airbnb Inc., the hosts and guests both benefit by increasingly participating in the social platforms of the sharing economy through collaborative consumption and even CSR events [45].…”
Section: Consumer Citizenship Behaviormentioning
confidence: 99%
“…By considering the generation mechanism and the process of innovation performance in manufacturing enterprises with regard to customer preference and by referring to the existing literatures [32][33][34][35][36][37][38][39][40], in this paper we divide indicators for innovation performance in manufacturing enterprises into three categories: innovation process performance, that is, the efficiency of innovation activities; innovation output performance, that is, the effect of innovation activities; and innovation performance for customers' green preferences. In the end, the index is summed up respectively, as shown in Table 1.…”
Section: The Indicators For Innovation Performance In Enterprisementioning
confidence: 99%